جهود القدامى في تأصيل النحو العربي: دراسة تأصيلية تحليلية - Abdul Rahman, Adam; Yaacob, Solehah@Nik Najah Fadilah; Raufi, Shah Rukh (The Scientific Institute For Advanced Training and Studies, 2019)
This research aims at studying linguistic argumentation, the standardization and the derivation of Arabic grammatical rules based on four criteria: listening (from the Quran, Hadith, poetry and prose), al-Ijmaa (unanimous agreement of scholars), al-Qiyaas (reasoning by analogy) and al-Istishaab (the idea of an implied connection between a present and a previous one). Linguistic argumentation is defined as the study of the fundamentals of Arabic grammar by ancient grammarians. In a quest to analyze these criteria, the researcher focuses on the definition of each criterion with the varying points of agreement and disagreement among the various grammarians. To achieve this, the researcher employs two methodologies; rooting and analytical methodology. The rooting methodology explains how the ancient grammarians deduced Arabic grammatical rules using these four criteria while the analytical methodology analyzes some grammatical issues. In deducing the rules of Arabic grammar, the ancient grammarians relied on the principle of listening, especially the Quran and considered it as the most reliable of the four criteria.